2019
DOI: 10.21608/jpp.2019.36271
|View full text |Cite
|
Sign up to set email alerts
|

Response of Onion to Foliar Spraying with some Nutrients under Different Rates of Npk Fertilizers

Abstract: The experimental design was randomized complete block design (RCBD) with three replications. The treatments were (1) Nonfertilization, (2). Control treatment (120, 45, 25 kg/fed NPK), (3). Humic acid+ 100% NPK, (4). Potassin +100% NPK, (5) Calfruit + 100% NPK, (6) Humic acid+ Potassin +100% NPK, (7) Humic acid+ Calfruit + 100% NPK, (8) Potassin + Calfruit + 100% NPK, ( 9) Humic acid+ Potassin + Calfruit, (10). Humic acid+ Potassin + Calfruit + 25% NPK, (11) Humic acid+ Potassin + Calfruit + 50% NPK (12) Humic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…Data presented in Table (3 A) clearly showed that the mineral NPK rates did not significantly affect the bulbing ratio (%) in both seasons. Similar results were reported by Miah et al, (2005); Islam et al, (2007); Kandil et al, (2013-a); and Mohamed et al, (2019) who found that foliar spraying with calcium and potassium compounds individually and/or mixing together decreased the number of days to maturity as compared to 100% NPK alone. Concerning injection rates with nano NPK, data illustrated in (Table 3 A) revealed that injection rates with nano NPK significantly affected bulbing ratio only in the second season.…”
Section: A 3 Bulbing Ratio (%)supporting
confidence: 87%
“…Data presented in Table (3 A) clearly showed that the mineral NPK rates did not significantly affect the bulbing ratio (%) in both seasons. Similar results were reported by Miah et al, (2005); Islam et al, (2007); Kandil et al, (2013-a); and Mohamed et al, (2019) who found that foliar spraying with calcium and potassium compounds individually and/or mixing together decreased the number of days to maturity as compared to 100% NPK alone. Concerning injection rates with nano NPK, data illustrated in (Table 3 A) revealed that injection rates with nano NPK significantly affected bulbing ratio only in the second season.…”
Section: A 3 Bulbing Ratio (%)supporting
confidence: 87%
“…Hal tersebut menunjukkan bahwa semakin besarnya ukuran bahan tanam dengan jarak tanam yang optimum mampu menghasilkan pertumbuhan dan berat kering tanaman yang optimum. Hal tersebut disebabkan karena laju fotosintesis meningkat sehingga menghasilkan fotosintat yang lebih banyak dan laju fotosintesis dapat dipengaruhi oleh jumlah daun dan bobot kering tanaman (Mohamed et al, 2019). Hasil panen bawang putih berkurang dengan semakin kecil ukuran siung dengan semakin lebarnya jarak tanam (Tabel 3).…”
Section: Hasil Dan Pembahasanunclassified